Revisiting Vygotskian regressions as ‘Living’ processes in second language development: Narrative review - Ross, Beata (Journal of Language, Literature, Social and Cultural Studies, 2023)
The transient or intermittent nature of Vygotskian regressions in the field of Second Language Development (SLD) has been relatively overlooked. To address this gap, the study employs a narrative literature review approach to enrich the theoretical and practical foundations of this concept. It proposes that they should be read in the context of the so-called living process development. By embracing this construct, the study introduces alternative theoretical insights, framing regressions as living-dramatic-dialectical occurrences, arising from the collision and interweaving of a wide range of opposing forces seen as events in variable proportions and intensities during moments of crisis.